Governance networks shaping the G20 through inclusivity practices. Issue 4 (2nd October 2019) - Luckhurst, Jonathan
ABSTRACT: This article analyses how global governance networks contest, influence, and shape the Group of Twenty (G20) forum through the latter's growing inclusivity practices, with important effects on global economic governance norms and practices. These transnational networks include public, intergovernmental, private, and civil society actors that interact through professional 'ecologies.' Some network actors participate in the G20's official engagement forums, others contribute to G20 policy formulation and implementation in other ways, including member-state representatives and officials from international institutions. The research includes evidence from participant observation, semi-structured interviews, public statements, and document analysis, deploying analytical tools from social constructivism, discourse analysis, and the sociology of professions. It examines G20 policy-shaping capacities of global governance networks, especially on macroprudential financial regulation, sustainable economic growth, and sustainable development. The research finds that governance networks have contributed significantly to decentralising global governance authority by diversifying its actors since the 2008 financial crisis.